Adaptação da escala multidimensional de liderança no desporto - versão comportamentos atuais - para o contexto brasileiro de esportes coletivos - Barale, Rômulo Ferreira (2009)
The study of leadership has been raising interest of theorists since the 1920s with the postulates of Trait Theory. In the sports context, spectators and professionals in the area ascribe significant weight to the leadership process in promoting the efficiency of teams. The measurement of this phenomenon in sports can still be considered a methodological gap due to the inexistence of a reliable and valid measurement instrument for the Brazilian reality. The aim of this study was to adapt, for the national context, the instrument of evaluation of leadership styles of coaches, known as Multidimensional Scale of Leadership in Sports (EMLD) in the version Present behaviors which was filled in by the athletes. The EMLD was constructed and validated in Portugal by Gomes (2005). The semantic analysis of the items of the instrument was carried out by eight judges: 3 doctors and 2 masters in Psychology; 1 doctor in Medical Sciences, and 2 graduate students in the educational area. Subsequently, the adaptation and validation of the measurement instrument was conducted. 290 athletes from team sports took part in this stage of the study. They answered a questionnaire composed by EMLD and by additional data from the sample. The data were submitted to reliability calculus of the original factors of EMLD and to factorial analysis in order to verify the adaptation and validation of the instrument. The factorial structure was composed by 3 factors that accounted for 37.1% of the total variance. The reliability for the factor: Motivational/inspiring leadership and positive contingency was 0.79; and it was 0.81 for the factors: Negative feedback and Leadership by informal relationship/social and affective support . The use of the measurement is recommended for academic research purposes. The results were discussed in relation to the theoretical models of the topic, the limitations of the study were identified, and a research agenda was suggested.